Evaluating the impact of employer branding initiatives on talent acquisition at 10 Minute School - Mantua, Nayefa Sultana (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.